Internalization of Multicultural Islamic Education Values to Students in Junior High Schools (SMP) in Hinai Langkat District - Hanum, Aziza; Alfarabi, Muhammad; Firmansyah, Feri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aims of this study is to find out the Internalization of Multicultural Islamic Education Values to Students in Junior High Schools (SMP) In Hinai Langkat District. This study uses qualitative research. The result of this study shows that the programs for junior high schools (SMP) throughout Hinai District in internalizing the values of multicultural Islamic education for students are the application of multicultural Islamic education values in the learning process, multicultural-based extracurricular activities at school, a multicultural school environment, and school rules and regulations that accommodate the values of differences in diversity. Furthermore, this program will be applied to school activities in implementing multicultural Islamic education for students. As for the implementation of the activities of junior high schools (SMP) throughout the Hinai sub-district in internalizing the values of multicultural Islamic education for students including teacher activities in teaching, school habituation activities, teacher exemplary behavior, school activities with historical, gender and cultural approaches and activities such as reading the Qur'an and praying before studying, praying, infaq, Ramadan activities and celebrating Islamic holidays. These activities instill the values of multicultural Islamic education so that students will become tolerant, appreciative, compassionate, and plural among fellow school members. Obstacles in applying the values of multicultural Islamic education include students' personalities and different cultures, the lack of depth in religious learning and the heterogeneous ethnic backgrounds of students. While the supporting factors in internalizing the values of multicultural Islamic education in schools include the existence of religious facilities such as prayer rooms and spaces for non-Muslim worship, the enforcement of school culture that applies discipline in school rules, and school activities that apply Islamic educational values multicultural in students.